Green LED as an Effective Light Source for Curing Acrylate-Based Dental Resins in Combination with Irgacure 784 - Katalin Bukovinszky; Melinda Szalóki; István Csarnovics; Istvan Szabó; Sándor Kéki; Miklós Nagy; Csaba Hegedűs (Advances in Condensed Matter Physics)
Low intensity green light emitting diodes (LED) were shown to be an effective light source to induce the photopolymerization of an acrylate-based photocurable dental restorative resin mixture of bisphenol A glycerolate dimethacrylate (BisGMA), triethylene glycol dimethacrylate (TEGDMA), and diurethane dimethacrylate (UDMA), in combination with fluorinated diaryl titanocene (Irgacure 784). Dental matrices were prepared by the LED light source at different intensities. The mechanical properties, such as Vickers microhardness, compressive strength, diametric tensile strength, flexural strength, and E-modulus of the created samples, were investigated. The kinetics of the photopolymerization was followed by Raman spectroscopy and conversion values were determined. It was found that, despite its narrow-emission range centered at a wavelength of 531 nm, the green LED light source is suitable for the preparation of dental matrices with good mechanical properties and high conversion values.